2018
DOI: 10.1016/j.bbadis.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet proteins and metabolic diseases

Abstract: Lipid droplets (LDs) are ubiquitous cellular organelles for lipid storage which are composed of a neutral lipid core bounded by a protein decorated phospholipid monolayer. Although lipid storage is their most obvious function, LDs are far from inert as they participate in maintaining lipid homeostasis through lipid synthesis, metabolism, and transportation. Furthermore, they are involved in cell signaling and other molecular events closely associated with human disease such as dyslipidemia, obesity, lipodystro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 407 publications
1
113
0
Order By: Relevance
“…Another suggested mechanism involved in maintaining LD homoeostasis is altered lipolysis. Several genes involved in lipolysis, including ATGL , CGI‐58 , HSL , LAL and MGL , were tested . However, oxLDL treatment had no significant effect on the genes associated with lipolysis (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another suggested mechanism involved in maintaining LD homoeostasis is altered lipolysis. Several genes involved in lipolysis, including ATGL , CGI‐58 , HSL , LAL and MGL , were tested . However, oxLDL treatment had no significant effect on the genes associated with lipolysis (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…32 LD accumulation is closely associated with human metabolic syndrome including atherosclerosis. 26,33 Thus, increased levels of LDs can signify either an increase in LD biogenesis or a disruption in the downstream degradation pathway (lipolysis and lipophagy). 34 In our study, oxLDL had no significant effect on LD biogenesis or lipolysis and we postulated that Autophagy is a highly conserved cellular homoeostatic 'housekeeping' process and it plays a critical role in the clearance of damaged organelles to maintain cell stability and metabolic homoeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though no specific LD targeting signal has been found yet, LD-associated proteins that directly target to LDs usually contain a hydrophobic domain or amphipathic a-helix(17, 18). For instance, LD resident protein in plants, oleosin, is proposed to comprise an N-terminal amphipathic domain, a central hydrophobic domain, and a C-terminal amphipathic a-helical domain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to study the proteins associated with LDs to unveil the role of LD in biological processes as well as human metabolic diseases. To date, over 100 proteins have been found on LDs and some of them have been proved to be associated with human diseases(17, 18). However, thus far, there has been no report on identification of LD-associated proteins derived from noncoding transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Except triacylglycerol (TAG), neutral lipids in LDs also include cholesterol ester, retinyl ester, wax ester, and polyhydroxyalkanoate (PHA)/polyhydroxybutyrate (PHB). Therefore, abnormal LD dynamics as well as ectopic lipid storage have been directly linked to many metabolic syndromes, such as obesity, fatty liver, and atherosclerosis, and diabetes [34][35][36]. We and others have previously reported that several strains of bacteria contain LDs and identified their main functions [37][38][39][40].…”
mentioning
confidence: 99%